#PraCegoVer: Investigating the description of visual content in Brazilian online social media - Sacramento, Carolina; Nardi, Leonardo Luís da Silva; Ferreira, Simone Bacellar Leal; Marques, João Marcelo dos Santos (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
Visual content is strongly present in online social media. To ensure the accessibility of these contents to screen reader users, it is necessary to provide alternatives. In this paper, we report an initial investigation about the practices of visual content description in Brazilian online social media by examining the interfaces of the four most used in the country (YouTube, Facebook, WhatsApp, and Instagram) and surveying the description habits adopted by sighted users and the difficulties faced by screen readers users in understanding visual content. For this purpose, we conducted online surveys with sighted and visually impaired social media users. The results showed, among other aspects, that most sighted users do not describe visual content and even those that describe it, have difficulties to create the alternatives, mainly because they don’t know what should be included or how to elaborate them. Moreover, for screen reader users, the greatest difficulty is the lack of alternatives for visual content provided by people. From the results, were identified actions and improvements to be adopted in the interfaces of online social media, in order to make them more inclusive to the Brazilian visually impaired.